Financial Statements Analysis and Reporting - Lessambo, Felix I. (Springer International Publishing, 2018)
Through a mixture of concepts and examples, this book demystifies the variety of elements of financial accounting and uncovers the need-to-know information for certification in this field. This book covers the two aspects of financial statement analysis, namely quantitative and non-quantitative analysis. Concluding with helpful case studies, the book will appeal to students and academics of financial accounting.